Selection of exercises for physical development for first-year male students of Duy Tan University in Danang, Viet Nam - Nguyen Xuan Hung; Nguyen Huu Anh Khoa (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.